Immune Checkpoint Inhibitor-Induced Central Diabetes Insipidus: Looking for the Needle in the Haystack or a Very Rare Side-Effect to Promptly Diagnose? - Barnabei, Agnese; Strigari, Lidia; Corsello, Andrea; Paragliola, Rosa Maria; Falzone, Luca; Salvatori, Roberto; Corsello, Salvatore Maria; Torino, Francesco (Frontiers in Oncology, 2022)
Immune checkpoint inhibitors have improved the survival in patients affected by an increasing number of malignancies, but they may also trigger various autoimmune side-effects, including endocrinopathies. Very rarely, immune checkpoint inhibitors have been reported to cause central diabetes insipidus. However, with their expanding use, the likelihood that oncologists will face this endocrine adverse event is expected to increase. By reviewing the limited literature on central diabetes insipidus induced by immune checkpoint inhibitors, some inconsistencies emerge in the diagnosis and the management of patients presenting with this toxicity, together with difficulties related to classifying its severity. Until now, specific guidelines on the management of central diabetes insipidus induced by immune checkpoint inhibitors are lacking. In clinical practice, endocrinological consultation may relieve medical oncologists from difficulties in treating this side-effect; oncologists, however, remain responsible for its early diagnose and the management of the causative drugs. To this aim, some practical suggestions are advised for the multidisciplinary management of cancer patients presenting with central diabetes insipidus induced by immune checkpoint inhibitors.